Building penetration loss measurements and modelling in the 900 and 2100 MHz band for smart meter installation - Owens, David; Ansari, Shuja; Cruickshank, Haitham; Tafazolli, Rahim; Imran, Muhammad Ali (Frontiers in Communications and Networks, 2022)
One of the most significant applications of Internet of Things are smart meters with wireless capabilities. Smart gas and electricity meters can capture half-hourly pricing and consumption data and send automated meter readings to your energy provider, in contrast to regular meters that can only register a running total of energy used. However, the legacy regular meters were not installed with wireless connectivity in mind and are usually found in hard-to-reach places for wireless radio coverage. To understand these scenarios, this paper provides signal strength measurements conducted at the Building Research Establishment determining building penetration losses in both 900 and 2,100 MHz band. We then present a building penetration loss model using these measurements that is practical and cost effective when compared to traditional statistical propagation loss models.